Giant Suprasellar Rathke's Cleft Cyst Mimicking Craniopharyngioma: Implications for a Spectrum of Cystic Epithelial Lesions of Ectodermal Origin - Choudhry, Osamah J.; Choudhry, Asad; Patel, Smruti K.; Baisre, Ada; Eloy, Jean Anderson; Liu, James K. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Cystic epithelial lesions such as Rathke's cleft cysts (RCCs) and craniopharyngiomas may be difficult to distinguish on a clinical, radiographic, and sometimes histopathological basis. We describe a case of a giant 6.5 cm suprasellar cystic lesion that was presumed to be a craniopharyngioma based on the neuroimaging findings. The lesion extended from the anterior skull base and sella turcica to the lateral ventricle and sylvian fissure resulting in obstructive hydrocephalus. Complete surgical removal of the suprasellar lesion was achieved using an extended frontotemporal transbasal skull base approach. Intraoperatively, the cyst wall was thickened and partially calcified, resembling a craniopharyngioma. However, the histopathological examination revealed findings most consistent with a RCC with additional features of extensive squamous metaplasia, metaplastic bone formation, and chronic inflammation. The case raises the issue of whether there is a pathologic continuum of parasellar ectodermal lesions which may account for the overlap of features and transitional states. In this report, we discuss the possible spectrum between RCCs and craniopharyngiomas, and also emphasize the importance of complete resection of the cyst wall in RCCs that exhibit squamous metaplasia, inflammation, or ossification to minimize the probability of recurrence.
Keywords: Rathke's cleft cyst; craniopharyngioma; suprasellar lesions; epithelial cyst